Typification of names in the genus Thymus (Lamiaceae) - Bartolucci, Fabrizio; Walter, Johannes (Phytotaxa, 2015)
Nomenclatural types for 30 names of the genus Thymus are designated here. The following names are lectotypified: Th. adriaticus, Th. albanus subsp. magellensis, Th. alsarensis, Th. alsarensis var. paucisetus, Th. belgradiensis, Th. benacensis, Th. boissieri var. ciliatopubescens, Th. brevicalyx, Th. britannicus, Th. chaubardii subsp. subisophyllus, Th. collivagus, Th. drucei, Th. istriacus, Th. froelichianus subsp. allionii, Th. lanicaulis, Th. lanuginosus var. pannonicus f. nicaeensis, Th. longicaulis var. freynii, Th. longicaulis var. salonitanus, Th. longidens var. drabiscensis, Th. moesiacus var. turcicus, Th. neglectus, Th. poliothrix, Th. pseudoatticus, Th. pseudolanuginosus, Th. sarntheinii, Th. serpyllum var. arcticus, Th. sepyllum var. ligusticus, Th. serpyllum var. vallesiacus, Th. thracicus var. byzantinus and Th. zetlandicus. Furthermore the new combination Thymus zygiformis var. magellensis is proposed.